Comparison between the conventional technique after third molar extraction and the use of fibrin-rich plasma associated with ozone therapy: case report (Research, Society and Development, 2021)
Third molars are usually the last teeth to erupt into the oral cavity, in which there is evidence of an absence of spaces in the dental arches, commonly leading them to be found in position as impacted and/or impacted. In these cases, some postoperative complications are frequent, with the presence of signs and symptoms, such as pain, edema, trismus, alveolitis, local bruises and bleeding. This paper aims to report a case in the literature of complementary treatments with platelet-rich fibrin (PRF) and ozonized oil in the extraction of third molars compared with the conventional technique. A search for scientific articles was performed in the PubMed and SciELO databases for scientific basis and construction of the clinical case report. Male patient, 20 years old, with chief complaint of painful symptoms in the lower third molars. Upon anamnesis, clinical and radiographic examination, extraction of teeth 38 and 48 semi-enclosed was indicated and complementary treatment was proposed with the Platelet-Rich Fibrin (PRF) technique and topical use of ozonized oil after extraction in the alveolus 48 compared with the technique conventional in alveolus 38. Symptomatic and clinical improvements were observed in region 48 compared to region 38 after 7 days of surgery. Fibrin-rich plasma associated with topical use of ozonized oil proved to be effective in this case of signs and symptoms after surgery and further studies should be carried out to create a clinical treatment protocol.